2018
DOI: 10.1071/an16601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herbage allowance on productive and reproductive responses of primiparous beef cows grazing on Campos grassland

Abstract: The effects of two levels of herbage allowance (HA, kg DM/kg liveweight (LW)) on forage mass and chemical composition, cow body condition score, cow LW, stocking rate, productive and reproductive responses were evaluated during two consecutive years. Eighty primiparous spring-calving beef cows were allocated to a completely randomised block design of two HA that had an annual average of 2.5 (low) and 4.0 kg DM/kg LW (high) from –150 to 195 days postpartum. The grazing system was continuous, and the put-and-tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Both allow for greater herbage intake in HHA during the drought. This observation confirms other studies, whose overall results show that higher HHA increases animal productivity as a whole (Claramunt et al, ; Do Carmo et al, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Both allow for greater herbage intake in HHA during the drought. This observation confirms other studies, whose overall results show that higher HHA increases animal productivity as a whole (Claramunt et al, ; Do Carmo et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Long‐term experiments in Brazil and Uruguay have shown that herbage allowance (kilograms of herbage dry matter available per kilogram of animal live weight) (Allen et al, ; Sollenberger, Moore, Allen, & Pedreira, ) is a key variable in grazing management that can be regulated to significantly increase current productivity and income (Claramunt, Fernández‐Foren, & Soca, ; Da Trindade et al, ; Do Carmo, Sollenberger, Carriquiry, & Soca, ; Soares et al, ). Higher herbage allowance corresponds with a taller sward.…”
Section: Introductionmentioning
confidence: 99%
“…Crossbred Angus and Hereford cattle increased kg of calf weaned per cow and cow BCS (Do Carmo et al, 2018), which confirms previous results (Morris et al, 1987). The farm stocking rate was unaffected by pasture management on this farm (Do Carmo et al, 2018) but had to be reduced by 25% in HHA compared with LHA when primiparous cows grazed on shallow soils (Claramunt et al, 2017). In this second farm, precipitation during springsummer had a huge effect on herbage yield.…”
Section: Managing Herbage Allowance and Cow Body Condition In Campos supporting
confidence: 86%
“…In this second farm, precipitation during springsummer had a huge effect on herbage yield. The stocking rate in HHA was lower, but the cow pregnancy rate (88 vs. 59%), calf weaning weight (194 vs. 175 kg;Claramunt et al, 2017), production per unit area, and production efficiency (g calf/MJ energy consumed per cow and per year) were higher in HHA than in LHA (Do Carmo et al, 2016). High HA led to moderate improvements in cow BCS (0.5 units) and energy intake (11%) during autumn.…”
Section: Managing Herbage Allowance and Cow Body Condition In Campos mentioning
confidence: 90%
See 1 more Smart Citation